2022
DOI: 10.3389/fmicb.2022.853440
|View full text |Cite
|
Sign up to set email alerts
|

The Mycoplasma spp. ‘Releasome’: A New Concept for a Long-Known Phenomenon

Abstract: The bacterial secretome comprises polypeptides expressed at the cell surface or released into the extracellular environment as well as the corresponding secretion machineries. Despite their reduced coding capacities, Mycoplasma spp. are able to produce and release several components into their environment, including polypeptides, exopolysaccharides and extracellular vesicles. Technical difficulties in purifying these elements from the complex broth media used to grow mycoplasmas have recently been overcome by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 163 publications
0
7
0
Order By: Relevance
“…Previous studies have identified some virulence-associated genes of M. bovis involved in adhesion ( 8 ), invasion ( 9 ), peroxide production ( 10 ), biofilm formation ( 11 ), avoiding phagocytosis of neutrophil granulocytes and macrophages ( 12 ), modulating immune responses of the host by immunoglobulin-binding proteins ( 13 ), and degrading neutrophil extracellular traps through nucleases ( 14 , 15 ). Recently, the concepts of Mycoplasma secretome and releasome have been proposed, and several secreted proteins were found in many Mycoplasma species ( 16 ). It is generally assumed that the components released into the culture supernatant or extracellular environment including enzymes, polypeptides, exopolysaccharides, and extracellular vesicles constituted the secretome of Mycoplasma .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified some virulence-associated genes of M. bovis involved in adhesion ( 8 ), invasion ( 9 ), peroxide production ( 10 ), biofilm formation ( 11 ), avoiding phagocytosis of neutrophil granulocytes and macrophages ( 12 ), modulating immune responses of the host by immunoglobulin-binding proteins ( 13 ), and degrading neutrophil extracellular traps through nucleases ( 14 , 15 ). Recently, the concepts of Mycoplasma secretome and releasome have been proposed, and several secreted proteins were found in many Mycoplasma species ( 16 ). It is generally assumed that the components released into the culture supernatant or extracellular environment including enzymes, polypeptides, exopolysaccharides, and extracellular vesicles constituted the secretome of Mycoplasma .…”
Section: Introductionmentioning
confidence: 99%
“…Despite our efforts, we failed at expressing active MIB-MIP systems from distantly related Mollicutes in Mferi, most likely due to problems related to the export of the system to the membrane. Despite many years of research, the protein export systems of Mollicutes are poorly characterized 73 . Most MIP proteins analyzed in this work contain a classic lipoprotein signal peptide (type II signal peptide), which consist of a positively charged N-terminal region, followed by a central hydrophobic area and a polar C-terminal region (lipobox) 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Secreted proteins play a crucial role in the interaction between bacteria and their environment, including host organisms. Previous studies have reported that secreted proteins in Mycoplasma species are released through various mechanisms such as polypeptides, exopolysaccharides, and extracellular vesicles [48]. Despite the identification of these secreted proteins, their specific functions remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%